ЛИБЕРТАРИЗМ И МОРАЛЬ - ДЫШКАНТ, Т. Н. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
На современном этапе развития общества либертарианское направление становится доминирующим, не только в области экономики, но и во всех иных сферах общественной жизни. Поскольку неолибералы доводят свой экономический либерализм до этической спецификации, возникает потребность анализа практической философии неолиберализма. Сделан вывод о непоследовательности неолибералов в разработке своей системы ценностей, что приводит к исчезновению даже такого основополагающего понятия как свобода. Ключевые слова: Дишкант Т.М. ЛІБЕРТАРІЗМ І МОРАЛЬ На сучасному етапі розвитку суспільства лібертаріанський напрямок стає домінуючим, не тільки у сфері економіки, але й усіх інших сферах суспільного життя. У зв’язку з розширенням у неоліберальній теорії економічного лібералізму до етичної специфікації, виникає потреба аналізу її практичної філософії. Зроблено висновок про непослідовність неолібералів при розробці своєї системи цінностей, що призводить до зникнення навіть такого основного поняття як свобода. Ключові слова: лібертарізм, вільний ринок, «негативна» свобода, індивідуалізм. Dyshkant Т. N. LIBERTARISM AND MORAL On the modern stage of development of society libertarian direction becomes dominant, not only in area of economy but also in all other spheres of public life. As libertarians takes the economic liberalism to ethics specification, there is the necessity of analysis of practical philosophy of libertarianism. The freedom understood as independence is the fundamental value of this direction. The open market built on principles of honest competition and presence of private property can secure her only. The presence of all above-mentioned conditions by unintentional way will provide a beneficence societies and spiritual development of man. However by the basic law of the society built exceptionally on a market exchange without taking into account social component, there is the law of maximal profits. It is instrumental in that market, all farther walks away from procedural honesty. There are processes which are instrumental in elimination, both freedom of markets processes and individual freedom. A conclusion is thus done about inconsistentness of libertarians in development of the system of values that results in disappearance even such fundamental concept as freedom. Key words: libertarism, free market, «negative» freedom, individualism.